Answer: x = 4 and x = -3/2
Procedure:
1) Given: 2x^2 - 5x - 12 = 0
2) Multiply both sides by : 2(2x^2) - 2(5x) - 2(12) = 0
3) Rearrange: (2x)^2 -5(2x) - 24 = 0
4) Notice that the common factor is (2x)
5) Set the parenthesis with the common factor inside:
(2x ) (2x ) =0
6) The first sign is the same sign of the second term of the trinomial, which is negative, the second sign is the product of the signs of the second and the third terms of the polynomial, which is (-)*(-) = + (positive)
(2x - )(2x + ) = 0
7) find two numbers that sum up - 5x and its product is -24.
- 8 + 3 = - 5
(-8)(+3) = -24
=> the numbers in the factors are -8 and +3
(2x - 8) (2x + 3) = 0
That is the factored equation. Now you can solve
8) a) 2x - 8 = 0 => 2x = 8 => x = 8/2 => x = 4
b) 2x + 3 = 0 => 2x = - 3 => x = - 3/2
Answer: the two solutions are x = 4 and x = -3/2
Answer:
c
Step-by-step explanation:
Answer:i would help but the picture is tooooo blurry
Step-by-step explanation:
Answer:
This statement is true.
Step-by-step explanation:
The absolute value is how far the number is from zero, so how many steps will it take on a number line to get from that particular number to zero?
Since you can't have negative steps, The -13 in absolute value would be 13.
The -(-13) is the same thing as saying -1 ( -13 ). Since negative times a negative is a positive, 13=13 is a true statement.
Answer:
2 inches
Step-by-step explanation:
x= smallest
3x=largest
2x=medium
x+3x+2x=12
6x=12
x=2
so smallest is 2
largest is 6 (3x)
medium is 4 (2x)
2+6+4=12